2014
DOI: 10.4187/respcare.03605
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Elimination and Oxygen Consumption in Mechanically Ventilated Children

Abstract: BACKGROUND: Accurate measurement of carbon dioxide elimination (V CO 2 ) and oxygen consumption (V O 2 ) at the bedside may help titrate nutritional and respiratory support in mechanically ventilated patients. Continuous V CO 2 monitoring is now available with many ventilators. However, because normative data are sparsely available in the literature, we aimed to describe the range of V CO 2 and V O 2 values observed in mechanically ventilated children. We also aimed to examine the characteristics of V CO 2 val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Alteration of minute ventilation changes EtCO 2 and VCO 2 in opposite directions, while changes in Qp or metabolism move EtCO 2 and VCO 2 in the same direction. However, in steady‐state conditions, when metabolism and minute ventilation are maintained at a constant, carbon dioxide elimination and, hence VCO 2 , represents an assessment of Q p and by extension CO in patients with normal cardiac physiology and anatomy . Among critically ill patients on mechanical ventilation and sedation, there may be very little variation in metabolic rate and minute ventilation at any given time within each individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of minute ventilation changes EtCO 2 and VCO 2 in opposite directions, while changes in Qp or metabolism move EtCO 2 and VCO 2 in the same direction. However, in steady‐state conditions, when metabolism and minute ventilation are maintained at a constant, carbon dioxide elimination and, hence VCO 2 , represents an assessment of Q p and by extension CO in patients with normal cardiac physiology and anatomy . Among critically ill patients on mechanical ventilation and sedation, there may be very little variation in metabolic rate and minute ventilation at any given time within each individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Under stable minute ventilation and metabolic conditions, VCO 2 becomes a very sensitive indirect indicator of Q p and by extension cardiac output in patients with normal cardiac physiology and anatomy. [8][9][10] Volumetric capnometry correlates well with Q p in patients with stable single ventricle physiology and with Q p and cardiac output in patients with structurally normal hearts. In contrast, poor correlation between cardiac output and VCO 2 is seen in patients with single ventricle physiology and significant intracardiac shunts.…”
Section: Discussionmentioning
confidence: 93%
“…e sample size was calculated according to a previous study [13], and assuming a middle effect size and an α error of 0.05, a sample size of 25 would have 80% power to detect the difference between the modes. Allowing for the 20% dropout rate, the sample size was increased to 30.…”
Section: Discussionmentioning
confidence: 99%
“…is approach assumes that the VO 2 of respiratory muscles varied with and without ventilatory support [11,12]. In addition, VCO 2 and VO 2 in mechanically ventilated patients can be measured using an indirect calorimeter [13]. A study reported significantly increased WOB in terms of energy expenditure (EE) and VO 2 during T-piece breathing compared with those in the PSV mode in critically ill patients [14].…”
Section: Introductionmentioning
confidence: 99%